Liquid metal coil. (August 2022) - Ye, Jiao; Xing, Ze-Rong; Gao, Jian-Ye; Liu, Jing
Abstract: Metal coils are typically used as motors, inductors, transformers, and loop antennas, which are essential and ubiquitous elements in electronics. With the improvement of living standards and the demand for compliant technologies, flexible electronics are thriving as new frontiers in diverse areas. Along with that, various soft circuits and electronic components are urgently required to replace those traditional rigid ones, in order to tackle existing challenges. Among those materials to realize device flexibility, room temperature liquid metals are playing ever important roles instead of conventional metal components due to their outstanding fluidity, large conductivity, and non-toxicity. In this review, we summarized and classified the transformable properties of liquid metal coils (LMCs) as four fundamental passive electronic components: resistor, capacitor, inductor, and memristor. The fabrication methods of LMCs are illustrated. Then we concluded LMCs' contributions to soft actuation, flexible sensing, antenna, and so on, which would be conducive to the fields such as wearable and implantable devices, soft robotics, and medical instruments. Finally, the current challenges in LMC's practical applications and outlook have been discussed. Graphical Abstract: ga1